1786 Vt. Acts, Oct. Sess. 30 - (:unkn) unknown (My University, 1793)
Every non-commissioned officer and private had to "constantly keep himself provided with a good musket, with an iron or steel rod, a sufficient bayonet and belt, two spare flints, a priming wire and brush, and a knapsack; a cartridge box and pouch, with a box therein, sufficient to contain not less than twenty-four cartridges suited to the bore of his musket."664 Horsemen were required to provide themselves with "a pair of pistols, and sabre, and cartridge box to contain twelve cartridges for pistols."665 Cavalry officers needed "a pair of pistols, and sword."
Keywords: MILITIAS